Gradient hot melt adhesive spraying process for anti-oxygen permeability of can opening seaming
By adjusting the three-phase hot melt adhesive system and existing equipment processes, a gradient structure for sealing metal can rolls is formed, which solves the problem of oxygen permeation in metal can roll sealing, achieving efficient oxygen barrier and long-term sealing performance, and is suitable for the manufacturing of metal packaging containers.
Patent Information
- Application Number
- CN202511527660.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-24
- Publication Date
- 2025-12-19
AI Technical Summary
Oxygen permeation exists at the roll seal of existing metal cans. Existing sealant systems have limited ability to block oxygen, and improvements are costly and risky, making it difficult to improve oxygen permeation resistance without adding equipment or changing production cycles.
A three-phase hot melt adhesive system is adopted, combined with existing equipment and process control, to form a gradient structure in the roll seal, including a wetting layer with a low glass transition temperature, a dense network of high barrier polymers, and microencapsulated oxygen-consuming components. Through the combination of shearing, heat treatment and lubricating oil, a gradient structure of wetting layer-barrier layer-buffer layer is formed.
It significantly reduces oxygen permeability, improves long-term sealing reliability and oxygen permeation resistance, reduces oxygen permeation rate, extends barrier life, and achieves industrial feasibility without increasing equipment or changing production cycle.
Smart Images

Figure CN121155867A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of metal packaging container manufacturing, and specifically relates to a gradient hot melt adhesive spraying process for anti-oxygen permeation of a can mouth roll seal. BACKGROUND
[0002] As an important packaging form of beverages, food and nutritional products, metal cans are widely used in the industrial production of carbonated beverages, beer, dairy products and canned food due to their good mechanical strength, light resistance and processing adaptability. However, among the entire structure of the metal can, the roll seal formed by the roll seal of the can body and the can cover is always the weak link of the packaging system. The roll seal process combines the can body and the can cover through two roller presses, and fills the joint with sealing glue to achieve sealing. Although this structure can provide high mechanical strength, oxygen can easily penetrate into the can through the roll seal gap due to the overlapping of multiple layers of metal, the complex geometric morphology and the local micro-gap at the roll seal.
[0003] The prior art usually uses a single-component sealing glue, mainly based on ethylene-vinyl acetate copolymer (EVA), butyl rubber or other thermoplastic elastomers, which mainly functions to wet the metal surface and fill the gap to achieve initial sealing. However, this single-phase glue system has limited oxygen barrier capacity, and after long-term storage, the oxygen content in the can increases due to the high oxygen permeability of the material itself, the lack of barrier skeleton in the structure, and the relaxation of the glue layer under the action of thermal cycling and mechanical stress. In addition, although some modified sealing glue improves the oxygen permeability to some extent by adding fillers or barrier agents, it is difficult to form a functional gradient in the thickness direction of the roll seal due to the single formula and uniform distribution, and there are still obvious deficiencies in long-term oxygen permeation and interface durability.
[0004] At the same time, the optimization research on the roll seal process itself mainly focuses on the adjustment of the roll edge geometric size, roller pressing parameters and lubricating oil formula, with the main goal of improving the mechanical strength of the roll seal and reducing leakage, but rarely involves improving the anti-oxygen permeation performance of the roll seal through material and process coupling. Especially on existing industrial production lines, the equipment layout and process flow are basically fixed, and if new equipment needs to be introduced or the production rhythm needs to be greatly adjusted, it will result in extremely high modification cost and process risk. Therefore, how to reasonably design the sealing glue system and utilize the existing roll seal process conditions to form a gradient functional layer structure inside the roll seal without adding new equipment and changing the production rhythm, so as to effectively prolong the oxygen diffusion path, reduce the oxygen permeation rate and improve the long-term sealing reliability, has become a technical problem that needs to be solved in this field. SUMMARY
[0005] The application aims to provide a gradient hot melt adhesive spraying process for oxygen-impermeable can end sealing, which is superior to the prior art in oxygen barrier, aging stability, sealing reliability and industrial feasibility through the comprehensive design of three-phase system + gradient structure + existing equipment process control, and has outstanding practical value and popularization prospect.
[0006] The technical scheme adopted by the application is as follows: The gradient hot melt adhesive spraying process for oxygen-impermeable can end sealing comprises the following steps: In the cap making process, a multi-phase hot melt sealing adhesive is pre-coated on the inner wall of the can end curl, and the hot melt adhesive is composed of the following components: A phase: low glass transition temperature and low modulus polymer, used for gap wetting, and the melt viscosity is 2-4 Pa·s (160-180 DEG C); B phase: high barrier polymer weakly compatible with A phase, used for forming a dense barrier network, and the melt viscosity is 4-8 Pa·s (150-170 DEG C); C phase: microencapsulated reactive oxygen-consuming or end-capped particles, accounting for 0.5-5 wt% of the total amount, and the particle size is 3-8 mu m; Before sealing, the sealing adhesive area of the can cover is preheated by using the steam flushing or hot air device on the canning production line, so that the surface temperature is raised to 45-70 DEG C, so as to promote the wetting of A phase; Under the action of the first sealing roller, high shear conditions are provided, so that the B phase is oriented and enriched in the middle part of the adhesive layer, and the A phase penetrates into the metal interface; The second sealing roller is used to complete the sealing shaping, so that the outer layer and the inner layer maintain the A phase buffer, the middle layer maintains the oriented B phase network, and the C phase is gradually released during the sealing cooling stage; Thus, a wetting layer-barrier layer-buffer layer gradient structure is formed in the sealing seam along the thickness direction.
[0007] Among them, the steam flushing adopts 0.08-0.12 MPa saturated steam, and the dryness is controlled to be 0.85-0.95, so that the amount of condensed water on the surface of the sealing adhesive is 20-50 mu g, thereby inducing the spatial redistribution of A phase and B phase during the rolling process.
[0008] Among them, the first sealing roller is tightened by 5-10 mu m relative to the standard roll gap, so as to increase the shear rate and form a banded orientation structure of B phase in the adhesive layer.
[0009] Among them, the radial eccentricity of the first sealing roller is controlled to be 2-5 mu m, so as to produce periodic shear changes and promote the formation of a multi-layer barrier network of B phase in the adhesive layer.
[0010] Wherein, the volume of the sealing lubricating oil is controlled at 20-30 cSt, and is moderately polar, so that the lubricating oil selectively migrates A phase during the sealing process, and forms an enrichment layer at the outer interface of the sealing to improve flexibility.
[0011] Wherein, the amount of cooling air is adjusted at the outlet of the second sealing roller, so that the surface temperature of the sealing seam is reduced by 10-15℃ compared with the reference, thereby locking the B phase orientation structure.
[0012] Wherein, a periodic fluctuation of ±5-10% is introduced to the thickness of the sealing adhesive layer in the cap-making process, so that a B phase enrichment zone is formed in the thick area after sealing, and an A phase wetting zone is formed in the thin area, thereby obtaining an alternating gradient distribution.
[0013] Wherein, the wall material of the C phase microcapsule is polyester or polyurethane, which has the characteristic of softening at a temperature of 60-90℃, so that the C phase is released in a delayed manner during the sealing cooling stage.
[0014] As described above, due to the adoption of the technical scheme, the present application has the following beneficial effects: Compared with the existing sealing process using a single hot melt adhesive or a conventional sealing adhesive, the present application realizes the following beneficial effects without increasing additional equipment and changing the production rhythm by coupling the three-phase hot melt adhesive system with the existing sealing process: (1) In the present application, the B phase high-barrier polymer is oriented and enriched in the middle part of the adhesive layer under the action of high shear and micro eccentricity of the first sealing roller, forming a continuous barrier network; at the same time, the A phase migrates to the sealing interface, ensuring wetting and gap filling. Oxygen molecules must detour the complex microfibrillar network when penetrating the sealing, thereby significantly prolonging the diffusion path. Experiments have shown that the oxygen transmission rate of the whole can under the process of the present application is reduced by 35-50%, which is significantly better than that of the existing single-phase sealing adhesive.
[0015] (2) By steam flushing induction, roller pressure eccentric fluctuation and coating thickness micro-fluctuation, the present application spontaneously forms a functional gradient in the thickness direction of the sealing seam: the outer layer is a flexible A phase enrichment layer, providing cushioning and anti-cracking; the middle layer is an oriented B phase barrier skeleton, providing main barrier; the inner layer is an A phase permeation layer, closely adhering to the metal surface, ensuring bonding. This gradient structure avoids the weakness of the traditional single adhesive layer, i.e. "high overall oxygen transmission rate and poor interface bonding", so that the sealing can still maintain high sealing performance after long-term storage and thermal cycling.
[0016] (3) The present application introduces a microencapsulated oxygen-consuming component into the adhesive layer, which utilizes the softening characteristics of the polyester or polyurethane wall material at 60-90℃, so that the C phase is gradually released after the sealing is completed and cooled, selectively consuming the residual oxygen in the sealing gap. This mechanism effectively reduces the risk of high initial permeation rate, so that the decay rate of barrier performance under accelerated aging conditions is less than 20%, which is significantly better than the existing technology.
[0017] (4) The present application can be implemented by only fine-tuning the parameters of the existing steam flushing or hot air device, setting the sealing roll gap and eccentricity, adjusting the cooling air flow, and optimizing the lubricating oil formula, without adding new hardware equipment, changing the production line layout and rhythm. Therefore, it has the feasibility and economy of direct introduction into industrial production. The prior art usually needs new equipment or special process to improve the barrier performance, which is high in cost and high in risk.
[0018] (5) In the comparative test, the sample of the present application has almost no leakage after drop impact and cold and hot cycle, and the cross-section observation shows that the damage mode is mainly metal tearing, the adhesive layer and the metal interface are tightly combined, and the debonding area is less than 5%; while the sample of the existing process is often interface debonding and overall relaxation of the adhesive layer, with high leakage rate. Therefore, the present application not only improves the barrier performance, but also improves the interface durability and overall structural stability.
[0019] In summary, the present application has achieved remarkable results superior to the prior art in oxygen barrier, aging stability, sealing reliability and industrial feasibility through the comprehensive design of three-phase system + gradient structure + process control of existing equipment, and has outstanding practical value and popularization prospect. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 The figure is a flowchart of the process of the present application. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the present application clearer, the present application is further described in detail below in combination with the drawings and examples. It should be understood that the specific examples described herein are only used to explain the present application and do not limit the present application.
[0022] Referring to Figure 1 The present application provides a gradient hot melt adhesive spraying process for oxygen barrier of can mouth sealing, which does not need to add new equipment, only needs to improve the sealing adhesive formula, and combines the process parameters of the existing steam flushing or hot air preheating device, the first roll and the second roll of the sealing machine, so as to form a gradient structure with a wetting layer-barrier layer-buffer layer along the thickness direction in the sealing seam, thereby significantly improving the oxygen barrier performance and long-term sealing property of the can mouth.
[0023] The hot melt adhesive adopts a three-phase system. Phase A is a low glass transition temperature, low modulus wetting and interstitial phase, such as ethylene-vinyl acetate copolymer (EVA, vinyl acetate content 14-28%) or polyolefin elastomer, with a softening point of 70-90°C and a melt viscosity of 2-4 Pa·s (160-180°C), ensuring rapid wetting of the metal surface and filling of micro-pores during sealing. Phase B is a high barrier skeleton phase, such as polyamide (PA6 or PA66), polybutylene terephthalate (PBT), or a blend thereof, with a melt viscosity of 4-8 Pa·s (150-170°C), capable of micro-fibrillar orientation under the high shear of the first sealing roller, and forming a dense barrier network in the middle of the adhesive layer. Phase C is a functional microcapsule, containing an oxygen-consuming agent such as sulfite, ascorbate or unsaturated compound, with a polyester or polyurethane shell, an average particle size of 3-8 μm, and an addition amount of 0.5-5 wt%. Phase C gradually releases active components during the sealing and cooling stage, consuming residual oxygen in the sealing seam, thereby prolonging the barrier life.
[0024] In the cover-making process, the above hot melt adhesive is prepared into a coating liquid with a solid content of 30 wt%, and is uniformly coated on the inner wall of the can cover flange by roller coating or doctor blade method, with a coating thickness controlled at 25-60 μm, preferably 30-45 μm. In order to further form a gradient structure, periodic thickness fluctuations of ±5-10% are introduced during the coating process by adjusting the doctor blade speed or roller speed, so that the sealing adhesive appears thick-thin alternation during the subsequent sealing process, so that the B phase and the A phase are enriched in the thick and thin areas respectively, and an alternating barrier band and wetting band is obtained.
[0025] On the canning production line, preheating is carried out using the existing steam flushing device before sealing. The steam pressure is 0.08-0.12 MPa, the dryness is controlled at 0.85-0.95, the distance between the nozzle and the cover surface is 8-12 mm, and the action time is 150-250 ms, so that the sealing adhesive layer temperature of the can cover flange inner wall rises to 50-65°C. During this process, 20-50 μg of condensed water is formed on the surface, which is rapidly vaporized during the subsequent first roller pressing, inducing spatial redistribution of A phase and B phase, promoting B phase to aggregate in the middle layer and A phase to distribute in the interface region. If the production line is not equipped with steam flushing, the existing hot air device can also be used for heating, with a hot air temperature of 90-110°C, an air speed of 6-8 m / s, and an action time of 200-300 ms, so that the sealing adhesive temperature rises to 45-60°C, which can also achieve the effect of preheating and softening.
[0026] During the crimping process, the first crimping roller bears the main high shear action. Under the condition of 300-600 cans / minute, the first roller gap is tightened by 5-10 μm relative to the standard value, and the crimping contact time is kept at 5-10 ms. Under this high shear condition, the B phase is oriented and microfibrillated in the middle of the adhesive layer to form a dense barrier network, while the A phase is squeezed into the metal contact interface to ensure interface wetting and sealing. In order to further enhance the multi-layer distribution of the B phase network, the first crimping roller allows a radial eccentricity or slight vibration of 2-5 μm. This periodic shear change forms a strip-shaped barrier structure in the adhesive layer, increasing the oxygen diffusion path.
[0027] In the operation of the second crimping roller, the roller gap is widened by 3-5 μm relative to the standard value for buffering and shaping to avoid excessive extrusion of the A phase. At the outlet of the crimping seam, the existing cooling air nozzle on the production line is used to control the air temperature at 15-20℃ and the air volume at 8-12 m³ / h, so that the surface temperature of the crimping seam is reduced by 10-15℃ compared to the case without cooling. This locks the orientation network of the B phase in time during the cooling process and prevents the network from dissipating due to subsequent temperature recovery.
[0028] In the lubrication of the crimping seam, food-grade white oil or synthetic ester oil with a viscosity of 20-30 cSt (40℃) and moderate polarity is used. During the crimping process, the lubricating oil can slightly dissolve the A phase, causing the A phase to further accumulate on the outer surface of the crimping seam, thereby forming a flexible accumulation band on the outer layer and improving the ability of the crimping port to resist mechanical impact and thermal cycling.
[0029] After the crimping is completed, the C phase microcapsules in the middle of the adhesive layer are released in a time-delay manner due to the gradual softening of the shell material in the range of 60-90℃. The released oxygen absorber reacts with the residual oxygen in the crimping seam, effectively reducing the oxygen content and further improving the anti-permeation performance of the crimping port.
[0030] Through the above process steps, the adhesive layer of the crimping seam naturally forms a continuous gradient structure of the outer layer A phase wetting band, the middle layer B phase barrier network, and the inner layer A phase buffer layer along the thickness direction, and is rich in time-delay released C phase in the middle layer, thereby realizing a crimping seal with stable structure, firm interface, and excellent barrier performance.
[0031] The implementation mechanism of the present application lies in the use of the poor compatibility of the three-phase hot melt adhesive system and the heat, shear, lubrication and cooling conditions existing in the sealing process, so that different components spontaneously form a gradient structure gradually transitioned in the thickness direction in the sealing seam. Specifically, the A phase of the hot melt adhesive is a low glass transition temperature and low modulus polymer, which has a low viscosity at the sealing temperature, can quickly wet the metal surface and fill the micro gap; the B phase is a high barrier polymer, which is weakly compatible with the A phase, and can easily be oriented and microfibrillated under high shear conditions, and stay in the middle of the adhesive layer due to its high viscosity; the C phase is a functional microcapsule, which contains oxygen-consuming or end-capped components, and the shell softens at 60-90°C, so it gradually releases during the cooling stage.
[0032] Before sealing, steam flushing or hot air heating raises the temperature of the adhesive layer to 45-70°C, and the steam preheating forms a small amount of condensed water on the surface of the adhesive layer. These condensed water vaporizes rapidly when the first sealing roller is pressed together, causing an instantaneous pressure gradient, which further promotes the spatial distribution of A and B phases. When entering the first sealing roller, the tight roller gap causes the sealing area to withstand strong shear, and the low viscosity A phase is forced to penetrate the metal interface, while the B phase is stretched into a filament or lamellar shape under shear and enriched in the middle of the adhesive layer. If the roller is slightly eccentric, periodic shear fluctuations will occur, causing the B phase barrier network to be distributed in strips or multiple layers, thereby increasing the diffusion path of oxygen molecules. After shaping through the second sealing roller, the moderately widened roller gap prevents the A phase from being squeezed out, and the cold air applied at the outlet reduces the temperature by 10-15°C, causing the oriented B phase to crystallize rapidly and be "frozen" in the middle layer, preventing structural relaxation due to rewarming, while the soft A phase in the outer layer maintains good cushioning performance.
[0033] The lubricating oil used during sealing is selected in terms of viscosity and polarity, which can slightly dissolve the A phase, causing the A phase to further migrate to the outer interface of the sealing and form a flexible outer interface layer, thereby improving the crack resistance and mechanical stability. After sealing is completed, the C phase microcapsules in the middle of the adhesive layer gradually release the internal oxygen-consuming components as the temperature drops, react with the residual oxygen in the sealing gap, reduce the local oxygen concentration, and further delay the oxidation of food and beverages.
[0034] In summary, the present application naturally forms a continuous gradient structure composed of an outer A phase wetting layer, a middle B phase barrier network and an inner A phase cushioning layer in the sealing seam through the coupling effect of material compatibility and process conditions, and the middle layer also contains a time-release C phase oxygen-consuming function. This structure can significantly prolong the diffusion path when oxygen permeates, and at the same time consume residual oxygen inside the sealing, thereby achieving a significant reduction in the oxygen transmission rate of the whole tank and stable maintenance of long-term barrier performance.
[0035] To verify the industrial applicability and performance advantages of the present invention, the process was compared and evaluated with the conventional single-phase sealant process in terms of oxygen transmission rate, aging stability, sealing reliability, and interface bonding quality, while keeping the existing equipment conditions of the production line unchanged. During the test, a variety of representative process combinations within the parameter range of the present invention were selected, including changes in formula proportion, differences in steam flushing or hot air preheating conditions before rolling, adjustment and eccentricity setting of the first rolling roller gap, cooling locking at the outlet of the second rolling roller, differences in lubricating oil viscosity and polarity, and fluctuations in sealant coating thickness, and the existing process was set as a control.
[0036] The purpose of this test is to prove that the process of the present invention can form a functional gradient adhesive layer in situ inside the rolling seam without adding any new equipment, significantly reduce the overall can oxygen transmission rate, quantify the influence order and synergistic effect of each key factor on performance, give the recommended process window, and verify the comprehensive advantages of the present invention in terms of aging retention rate, leakage rate, interface debonding rate, and mechanical resistance performance through comparison with the existing process. The test range covers typical production lines of tinplate and aluminum easy-open lid beverage cans (capacity 250-500 mL), with a rolling speed of 280-600 cans / min.
[0037] The evaluation indicators include the overall can oxygen transmission rate in the initial state, the oxygen transmission rate and increase after 4 weeks of accelerated aging at 38℃, 90% RH, as well as batch leakage sampling, cold and hot cycle reliability tests, and drop impact tests. The debonding area and failure mode of the adhesive layer in the rolling stack were evaluated by microscopic observation. All samples were from the same batch of substrates and adjuvants, the test environment and measurement calibration were consistent, and the process parameters such as steam dryness, lid surface temperature, roller gap adjustment, eccentricity, cooling temperature difference, lubricating oil properties, and coating thickness fluctuations were strictly recorded to ensure the scientificity and repeatability of the comparison results.
[0038] Based on existing research and theoretical analysis, the present invention process is expected to reduce the initial overall can oxygen transmission rate by more than 35%, the aging transmission rate increase by no more than 20%, significantly reduce the batch leakage rate, and stabilize the interface debonding area to less than 5%. Through this series of systematic comparison tests, the barrier effect and long-term stability of the process of the present invention can be intuitively demonstrated, and reliable data support can be provided for its mass production introduction in the metal packaging industry.
[0039] Specifically, the test premise and test methods include: Test object: 330 mL tinplate beverage cans (industry standard materials and thicknesses for can body / can lid), same batch of substrates.
[0040] Sealant system: Phase A (EVA / POE, Tg <−20°C, η=2–4 Pa·s @ 160–180°C) Phase B (PA6 / PBT or blend, η=4–8 Pa·s @ 150–170°C) Phase C (polyester / polyurethane shell microcapsule, D50=3–8 µm) Production line: existing steam flush / hot air, two lanes of sealing rollers, original lubricating oil supply, no new equipment added.
[0041] Sealing line speed: 280–600 CPM (see table).
[0042] OTR test: container method, 23°C / 50% RH, equivalent whole-can oxygen transmission rate, unit cm³ / (can·d); retest after aging: 38°C / 90% RH x 4 weeks.
[0043] Mechanical and sealing: 1.2 m drop x 10 times; cold and hot cycle ; 500 cans / batch leakage sampling.
[0044] Interface bonding: after cutting, 20x microscope to determine the percentage of debonding area of the adhesive layer.
[0045] Steam flush: saturated steam 0.08–0.12 MPa, dryness 0.85–0.95; record cover surface temperature and estimated condensate amount (µg).
[0046] Eccentricity / roll gap: take the production reference roll gap as 0, record the first roll “tightening (−) / loosening (+)” micron value; eccentricity measured by micrometer (µm).
[0047] The process parameter table is as follows:
[0048] Note: T1 is the combination of the “recommended window” of the invention; T2–T7 are “de-advantage / mismatch” comparisons of key factors within the scope of the invention; C0 is the control of industry conventional single-phase sealing glue + standard sealing parameters.
[0049] The test result table is as follows:
[0050] Note: OTR attenuation (↑%) = (after aging−initial) / initial.
[0051] “Debonding area (%)” is the percentage of visible debonding area of the adhesive layer at the interface of the sealing stack after cutting.
[0052] All batches meet the commercial sealing standard, but T1 is significantly better than the control and other combinations in terms of barrier and stability.
[0053] Result analysis: Synergistic effect of recommended window (T1): preheat temperature 60°C + steam dryness 0.90 produces about 30 µg condensate, first roller -8 µm tightening superimposed with 3 µm eccentricity, induces B-phase microfibrillation + zonal distribution; second roller outlet ΔT=12°C cooling lock prevents subsequent rewarming; medium polarity, 25 cSt lubricating oil selectively dissolves A-phase, outer layer enriched; ±8% thickness fluctuations converted into alternating gradient zones. Thus the lowest initial OTR=0.62, aging only +14%, leakage 0 / 500, interfacial debonding 2%.
[0054] B-phase content is one of the main factors (T2): reduce B-phase from 50% to 40%, otherwise unchanged, initial OTR rises to 0.78; microfibril network is sparse, aging sensitive (+18%). It is more optimal in the interval of 48-52% B-phase, and the barrier decreases significantly below this interval.
[0055] The "zonal network" brought by eccentric micro-vibration is irreplaceable (T3): cancel 3 µm eccentricity, initial OTR rises to 0.73, aging +18%. Controllable eccentricity of 2-3 µm can significantly increase the effective diffusion path.
[0056] Cooling lock is the key to stability (T4): remove ΔT cooling, initial OTR=0.76, after aging +28% (one of the most obvious deteriorations). Cooling 10-15°C at the second roller outlet is the key window to lock the orientation of B-phase.
[0057] Thickness fluctuations enhance alternating gradients (T5): remove ±8% fluctuations, initial OTR 0.71; the network is still there, but the "zone-valley" is weakened, aging +20%. It is recommended to retain periodic fluctuations of ±5-10% during the cover-making process.
[0058] Inductive effect of steam "moist heat" (T6): dryness 0.97 almost no condensation, initial OTR 0.75, aging +24%. Dryness 0.85-0.95 range, 20-50 µg condensate can significantly enhance A / B redistribution.
[0059] Lubricating oil viscosity / polarity mismatch can lag behind (T7): 40 cSt / low polarity oil causes A-phase to be difficult to move outward, and the outer layer is not tough enough, initial OTR 0.80, aging +25%, leakage 4 / 500. It is recommended to use 20-30 cSt, medium polarity, food-grade oil.
[0060] Therefore, the gradient hot melt adhesive spraying process for anti-permeable oxygen of can end sealing provided by the present application can in-situ form a functional gradient adhesive layer in the sealing seam by coupling the three-phase sealing adhesive system with the sealing process conditions without increasing new equipment, greatly improves the anti-permeable oxygen performance of the sealing, and meets the requirements of industrial production.
[0061] The above description is only the preferred embodiment of the present application, and is not intended to limit the present application. Any modification, equivalent replacement and improvement made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A gradient hot melt adhesive spraying process for preventing oxygen permeation during can opening sealing, characterized in that, Includes the following steps: During the cap-making process, a multiphase hot melt sealant is pre-applied to the inner wall of the cap's rolled edge. The hot melt sealant consists of the following components: Phase A: Low glass transition temperature, low modulus polymer, used for wetting and filling gaps, with a melt viscosity of 2–4 Pa·s (160–180℃). Phase B: A high-barrier polymer that is weakly compatible with Phase A, used to form a dense barrier network, with a melt viscosity of 4–8 Pa·s (150–170 °C). Phase C: Microencapsulated reactive oxygen-consuming or end-capped particles, accounting for 0.5–5 wt% of the total, with a particle size of 3–8 μm; Before sealing, the sealing area of the can lid is preheated using steam flushing or hot air equipment on the canning production line to raise its surface temperature to 45–70°C to promote A-phase wetting. Under the action of the first sealing roller, high shear conditions are provided, causing the B phase to undergo microfibrillation and enrichment in the middle of the adhesive layer, while the A phase penetrates into the metal interface. The second sealing roller completes the sealing and shaping process, ensuring that the outer and inner layers maintain the A-phase buffer, the middle layer maintains the oriented B-phase network, and the C-phase is gradually released during the sealing and cooling stage. This creates a gradient structure within the roll seal that continuously transitions along the thickness direction, consisting of a wetting layer, a barrier layer, and a buffer layer.
2. The gradient hot melt adhesive spraying process for preventing oxygen permeation during can opening sealing as described in claim 1, characterized in that: The steam flushing uses saturated steam at 0.08–0.12 MPa, with the dryness controlled at 0.85–0.95, so that the amount of condensate on the sealant surface is 20–50 μg, thereby inducing spatial redistribution of phase A and phase B during the rolling process.
3. The gradient hot melt adhesive spraying process for preventing oxygen permeation during can opening sealing as described in claim 1, characterized in that: The first sealing roller is tightened by 5–10 μm relative to the standard roll gap to increase the shear rate and enable the B phase to form a ribbon-like orientation structure in the adhesive layer.
4. The gradient hot melt adhesive spraying process for preventing oxygen permeation during can opening sealing as described in claim 1, characterized in that: By controlling the radial eccentricity of the first sealing roller to 2–5 μm, periodic shear changes are generated, promoting the formation of a multi-layer barrier network of the B phase in the adhesive layer.
5. The gradient hot melt adhesive spraying process for preventing oxygen permeation during can opening sealing as described in claim 1, characterized in that: The viscosity of the sealing lubricant is controlled at 20–30 cSt and is of medium polarity, which allows the lubricant to selectively migrate the A phase during the sealing process and form an enriched layer at the outer interface of the seal to improve flexibility.
6. The gradient hot melt adhesive spraying process for preventing oxygen permeation during can opening sealing as described in claim 1, characterized in that: Adjust the cooling airflow at the exit of the second sealing roller to reduce the surface temperature of the sealing seam by 10–15°C compared to the reference temperature, thereby locking the B-phase orientation structure.
7. The gradient hot melt adhesive spraying process for preventing oxygen permeation during can opening sealing as described in claim 1, characterized in that: In the cap manufacturing process, a periodic fluctuation of ±5–10% is introduced into the thickness of the sealant layer, so that after sealing, the thick area forms a B-phase enrichment zone and the thin area forms an A-phase wetting zone, thereby obtaining an alternating gradient distribution.
8. The gradient hot melt adhesive spraying process for preventing oxygen permeation during can opening sealing as described in claim 1, characterized in that: The wall material of the C-phase microcapsules is polyester or polyurethane, which has the property of softening at a temperature of 60–90°C, allowing the C-phase to be released with a delay during the roll-up cooling stage.
